The liver-alpha-cell axis after a mixed meal and during weight loss in type 2 diabetes. Issue 9 (9th September 2021) - Otten, Julia; Stomby, Andreas; Waling, Maria; Chorell, Elin; Ryberg, Mats; Svensson, Michael; Holst, Jens Juul; Olsson, Tommy
Abstract : Objective: Glucagon and amino acids may be regulated in a feedback loop called the liver-alpha-cell axis with alanine or glutamine as suggested signal molecules. We assessed this concept in individuals with type 2 diabetes in the fasting state, after ingestion of a protein-rich meal, and during weight loss. Moreover, we investigated if postprandial glucagon secretion and hepatic insulin sensitivity were related. Methods: This is a secondary analysis of a 12-week weight-loss trial (Paleolithic diet ± exercise) in 29 individuals with type 2 diabetes. Before and after the intervention, plasma glucagon and amino acids were measured in the fasting state and during 180 min after a protein-rich mixed meal. Hepatic insulin sensitivity was measured using the hyperinsulinemic-euglycemic clamp with [6, 6- 2 H2 ]glucose as a tracer. Results: The postprandial increase of plasma glucagon was associated with the postprandial increase of alanine and several other amino acids but not glutamine. In the fasted state and after the meal, glucagon levels were negatively correlated with hepatic insulin sensitivity (rS = −0.51/r = −0.58, respectively; both P < 0.05). Improved hepatic insulin sensitivity with weight loss was correlated with decreased postprandial glucagon response (r = −0.78; P < 0.001). Conclusions: Several amino acids, notably alanine, but not glutamine could be key signals to the alpha cell to increase glucagon secretion. Amino acids may be part of a feedback mechanism as glucagon increases endogenous glucose production and ureagenesis in the liver. Moreover, postprandial glucagon secretion seems to be tightly related to hepatic insulin sensitivity.